Industry specialization, diversity and the efficiency of regional innovation systems - Michael Fritsch; Viktor Slavtchev (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
Innovation processes are characterized by a pronounced division of labor between actors. Two types of externality may arise from such interactions. On the one hand, a close location of actors affiliated to the same industry may stimulate innovation (MAR externalities). On the other hand, new ideas may be born by the exchange of heterogeneous and complementary knowledge between actors, which belong to different industries (Jacobs externalities). We test the impact of both MAR as well as Jacobs externalities on innovative performance at the regional level. The results suggest an inverted u-shaped relationship between regional specialization in certain industries and innovative performance. Further key determinants of the regional innovative performance are private sector R&D and university-industry collaboration.
Keywords: O31; O18; R12; 330; Innovation; technical efficiency; patents; agglomeration concentration; specialization; diversity; regional analysis; Innovation; Region; Spillover-Effekt; Agglomerationseffekt; Patent; Forschungskooperation; Technische Effizienz; Deutschland